The Effect of Taxifolin on Acrylamide-induced Oxidative and Proinflammatory Brain Injury in Rats: A Biochemical and Histopathological Study - Ersoy, Alevtina; Yasar, Hasan; Tanoglu, Ceyda; Yazici, Gulce Naz; Coban, Taha Abdulkadir; Arslan, Yusuf Kemal; Suleyman, Halis (Indian Journal of Pharmaceutical Education and Research, 2021)
Purpose: Acrylamide is a well-known environmental toxic compound. Taxifolin belongs to the group of flavonoids that have antioxidant, antimicrobial, anti-inflammatory and anti-carcinogenic properties. In this study, we investigated the effect of taxifolin on acrylamide-related oxidative and proinflammatory brain damage. Methods: The experimental animals were divided into three groups: (1) those treated with acrylamide 20 mg/kg p.o., (2) those treated with taxifolin 50 mg/kg p.o. and acrylamide and (3) the control group. At the end of the experiment, the rat brain tissues were examined for the levels of Malondialdehyde (MDA), total glutathione (tGSH), tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β). A histopathological analysis was performed to detect the morphological changes in the brain. Results: Exposure to acrylamide caused a significant increase in the levels of MDA, TNF-α and IL-1β and a decrease in the values of tGSH, which indicates the presence of oxidative stress and inflammation in the brain tissue. Taxifolin treatment significantly reduced the levels of MDA and TNF-α and brought the mean values of IL-1β and tGSH close to those of the control group. The group that received acrylamide exhibited histopathological changes, such as neuronal degeneration, edema of microglia, dilated and congestive vessels and apoptotic inclusion. The use of taxifolin significantly improved the morphological changes in the brain tissue of the acrylamide-exposed rats. Conclusion: Acrylamide causes brain damage, inducing oxidative stress and inflammation. Due to its antioxidant and anti-inflammatory properties, taxifolin may be one of the agents that can reduce the neurotoxic effects of acrylamide.
Keywords: Acrylamide; Brain damage; Inflammation; Neurotoxicity; Oxidative stress; Taxifolin